Status of teachers in the English-speaking Caribbean : a survey of recent trends - Brown, Hazel ([Caricom Secretariat] [Georgetown]GY)
Provides a database on the terms and conditions of service of teachers in the Community to enhance the decision-making process of regional policy makers and educational planners. Seeks to assist the ILO and UNESCO in assessing progress towards the implementation of selected goals in the recommendation on the status of teachers.